Prospective teachers’ views on faculty members as content creators - Demirdağ, Seyithan; Nirwansyah, Anang Widhi; Muslim, Aji Heru; Bramantio, Bimo (Institute of Advanced Engineering and Science, 2025)
This study examines prospective teachers’ perceptions of faculty members as content creators in higher education, with a focus on how content development impacts effective teaching and learning. Using a qualitative descriptive phenomenological approach, the research explores the experiences of 26 senior students from diverse academic backgrounds at a university in Northwestern Turkey. The participants were selected through maximum variation sampling, representing fields such as special education, elementary education, science, social studies, preschool, and mathematics teaching. The findings reveal that prospective teachers value faculty members’ use of technology to create engaging, personalized learning experiences. Faculty expertise in digital content creation and contemporary teaching tools plays a key role in shaping students’ pedagogical development and boosting their confidence. However, challenges such as varying technological proficiency levels hinder some prospective teachers from fully integrating content creation into their future teaching practices. The study underscores the importance of faculty expertise and technological competence in teacher preparation. It advocates for comprehensive professional development programs to enhance educators’ content creation skills and encourages collaborations between faculty and technology experts to develop effective educational content. The study calls for addressing technological adoption barriers and equipping prospective teachers with necessary skills for effective 21st-century teaching. Future research should build on these findings with quantitative methods to further explore students’ perspectives on content creation.